Computer simulation of "Splash Control" and research of the Rip Entry technique in Competitive Diving - Qian, J.; Zhang, S.; Jin, H. (International Journal of Sports Science and Engineering, 2010)
The purpose of this study was to examine effects of different hand patterns used by divers on the minimization of splash at the instance of water entry for competitive diving. An impact model was developed with the human body modeled as a wedged solid object and the water as an ideal fluid. The equations of motion for the solid object were established with satisfactions of control functions and initial boundary conditions of the fluid. A finite element method was used to simulate the impact process in customized computational software. The results indicated a proportional relationship between the highest point of the unrestrained wave surface and the wedge angle during the impact. The simulation results indicated a "squared object" as the ideal shape for the water entry. In practice, instead of having palms facing each other to form a wedge at the water entry, the diver should internally rotate the arms and form a flat impact surface with the palms towards the water to effectively limit the water splash. Further mechanical analyses also suggested that, the palms should be maintained in a direction just opposite to the resultant velocity of the water in a "massaging" motion during the impact in order to effectively control the splash.